Foreign Investment Policy in Renewable Energy Post Job Creation Law - Aswin Pasaribu; Paskalis Agung Purnomo (Universitas Islam Balitar, Blitar, 2023)
Legal certainty in foreign investment in renewable energy is a priority factor and the most relevant for investment. Considering this, the Job Creation Law was born to overcome the problem of overlap and over-regulation. Through a normative juridical approach that is descriptive in analysis, research has produced that the policy of foreign investment in the field of renewable energy after the Job Creation Law has undergone significant changes in terms of foreign investor requirements, types of business fields that are closed for investment, investor facilities, and simplification of investment provisions, as a strategy to facilitate the entry of foreign investment in order to improve the investment ecosystem in Indonesia.